Macro-fiscal policy challenges and public investment in new EU member states - Gerd Schwartz; Ana Corbacho; Qiang Cui; Giovanni Ganelli; Paolo Manasse (EIB Papers, 2008)
Most new EU member states (NMS) need further fiscal adjustment to support economic growth and macroeconomic stability. In this context, achieving income convergence with other EU members rests more with maintaining productivity growth, attracting foreign savings, and improving investment efficiency than with increasing government spending (including for infrastructure). Additional institutional fiscal reforms, aimed at improving expenditure efficiency and facilitating private sector investment, will be needed to support these objectives. However, further fiscal adjustment and reforms do not necessarily need to depress public investment. New financing options for public investment - including from various EU funds and through public-private partnerships - can ease existing fiscal and macroeconomic constraints, but present both new opportunities and challenges that need to be handled carefully.
Keywords: 330; Finanzpolitik; Öffentliche Investition; Infrastrukturinvestition; EU-Staaten (Osteuropa)